Pengaruh Media Flascard Terhadap Daya Ingat Angka Anak Usia 3-4 Di Paud Aisyiyah Matahari Bersinar - Herlina Hadiyati Safariyah; Maimon Sumo; Musayyadah Musayyadah (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Utilizing flashcard media includes a positive affecton expanding children's cognitive improvement. The point of this inquire about is to degree how much impact flashcard media has on the numerical memory of children matured 3-4 a long time at PAUD Aisyiyah Matahri Bersinar, Waru Locale. The research methods used consist of quantitative, experimental and data collection techniques using observation and documentation. The data analysis technique used to test the research hypothesis uses the t test with the help of the SPSS 18 for Windows evaluation version program application. Research results: 1). Using flashcard media can improve the number memory of students at PAUD Aisyiyah Matahari Bersinar 2). There is an influence of flashcards on number memory in children aged 3-4 years. This means that flashcards have a big influence on the numerical memory of children aged 3-4 years. Keywords: Flashcard, Memory, Early childhood